2007
DOI: 10.1021/je700386c
|View full text |Cite
|
Sign up to set email alerts
|

Water Vapor Concentration Enhancement in Compressed Humid Nitrogen, Argon, and Carbon Dioxide Measured by Fourier Transform Infrared Spectroscopy

Abstract: Knowledge of the dew point of compressed humid gases is needed for many new technical applications, e.g., compressed air energy storage (CAES), humid air turbine (HAT), or zero emission power plants. A new method was developed to measure the dew point, expressed as vapor concentration enhancement factor, by Fourier transform infrared (FTIR) spectroscopy. This method has already been successfully applied to compressed humid air (Koglbauer and Wendland, J. Chem. Eng. Data 2007, 52, 1672-1677). Here, measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…While not all of the previous experimental studies of the dew point of H 2 O in compressed CO 2 reported uncertainties, those that did had relative uncertainties of several percent in the water content of the vapor phase. There is no reason to expect that the uncertainties of the other studies were any better.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…While not all of the previous experimental studies of the dew point of H 2 O in compressed CO 2 reported uncertainties, those that did had relative uncertainties of several percent in the water content of the vapor phase. There is no reason to expect that the uncertainties of the other studies were any better.…”
Section: Discussionmentioning
confidence: 93%
“…Existing experimental data for the water vapor enhancement factor f(T , p ) in compressed CO 2 at moderate pressures (below about 10 MPa) were reviewed in 2011 by Wheatley and Harvey . Especially at relatively low temperatures relevant to pipeline transport, the existing experimental data were found to be mutually inconsistent. A recent experimental study also covered the region of interest, but the dew‐point measurements at low temperatures had large uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…We expect the effect to be smaller for argon, as seen in the data presented in Refs. [4,5]. We conclude that ignoring the enhancement factor will not result in significant error.…”
Section: Humidity Generation Methodsmentioning
confidence: 76%
“…The preceding equations assume ideal-gas behavior and do not account for four effects: (1) the nonideal behavior of the carrier gas and water vapor, (2) intermolecular forces in the mixture of water vapor and carrier gas, (3) the action of the pressure on the condensed water (the Poynting effect), and (4) the solution of the carrier gas in the water (the Raoult effect). (See, for example, Hyland (1975), Wylie (1996), Koglbauer (2007), Koglbauer (2008), Lovell-Smith (2016.) Correcting Eq.…”
Section: The Enhancement Factormentioning
confidence: 99%